RESERVOIR PROPERTIES AND PROSPECTIVES OF LOWER PLIOCENE SEDIMENTS IN THE UMID AREA OF THE BAKU ARCHIPELAGO - Nasibova, G.; Mukhtarova, Kh.; Narimanov, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of this study is to investigate and analyze the reservoir properties of the Lower Pliocene sediments of the Baku Archipelago Umid area and its oil and gas potential. One of the latest studies in the Umid area was geological assessment of reservoir parameters for calculation of hydrocarbon reserves. The earlier obtained results made it possible to more reliably calculate hydrocarbon reserves and plan prospecting and exploration works in the right direction. Large gas condensate reserves were identified in 2009 in horizons V and VII of the Productive Series (PS). Thus, well 10 produced 1.2 million m3/day of gas and 150 tons of condensate from the depth interval of 6340-6356m. Considering that hydrocarbon fields of the South Caspian depression (SCD) are, as a rule, multilayered, this is a reason to predict presence of hydrocarbon accumulations in deeper strata as well. Variation patterns of reservoir properties, such as grain composition, carbonate content, porosity, permeability, density, propagation velocity of ultrasound waves in rocks were not comprehensively investigated in the previously conducted studies. The article studies impact of the structural and tectonic properties of the Umid uplift of the SCD Baku archipelago upon formation of a mud volcano on the southeastern periclinal subsidence. Taking into account impact of compressional stresses on the position of the fold vault and the crater of the mud volcano in connection with the syndepositional development of the uplift, a recommendation on the location of prospecting wells to deeper horizons is substantiated. Formation of reservoir properties of rocks is a function of tectonic stresses arising in them. Occurrence of secondary reservoir properties in rocks is highly probable in tectonically active zones. There is a stable inverse relationship between reservoir properties, carbonate and clay content, and a direct one - with the degree of grain sorting that make up the rocks. The issues considered in the article indicate a high probability of presence of hydrocarbon accumulations here in deeper horizons of the sedimentary section. In the future, based on our studies and geological and geophysical methods, it will be possible to thoroughly assess the prospects of deep-lying stratigraphic units of this area, and those identical to it.